Multi-organ comparison and quantification parameters of [18F]THK-5317 uptake in preclinical mouse models of tau pathology - Wanek, Thomas; Mairinger, Severin; Filip, Thomas; Löbsch, Mathilde; Stanek, Johann; Kuntner, Claudia (Frontiers in Physics, 2023)
Current small animal PET instrumentation provides sufficient resolution, sensitivity, and quantitative accurate information on the radiotracer distribution within the whole body. However, most preclinical imaging studies focus on disease-related organs of interest and do not use the total body information provided by small animal PET. In this study, we investigated the distribution of [ 18 F]THK-5317 (also referred to as (S)-[ 18 F]THK-5117), a radiotracer initially developed to visualize tau deposits in the brain, in two transgenic mouse models of tau overexpression and littermate controls at different ages and of both sexes. We compared multiple quantitative parameters of radiotracer uptake in multiple organs of mice to investigate sex, age, or strain-related differences. After intravenous administration, 60-minute dynamic PET scans were acquired, followed by venous blood sampling, organ harvesting, and metabolite analysis using radio-thin layer chromatography. Blood pharmacokinetics and metabolism of [ 18 F]THK-5317 significantly differed between males and females across all strains. Sex-related differences in organ VTs were identified from twoway ANOVA analysis. Organ-to-blood concentration ratios correlated well with organ VTs in all investigated organs. Following our workflow, a straightforward multiple-organ analysis of [ 18 F]THK-5317 uptake in mice was easily achievable. From the derived quantitative parameters, the organ-to-blood values correlate best with the calculated VTs. In light of actively incorporating the 3R´s principles into preclinical quantitative imaging, we propose that this workflow might be suitable to select novel radiotracer candidates before more complex kinetic models comprising invasive methods such as full arterial blood sampling for radiotracer quantification are applied.